2014
DOI: 10.1038/cddis.2014.462
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-320/RUNX2 axis regulates adipocytic differentiation of human mesenchymal (skeletal) stem cells

Abstract: The molecular mechanisms promoting lineage-specific commitment of human mesenchymal (skeletal or stromal) stem cells (hMSCs) into adipocytes (ADs) are not fully understood. Thus, we performed global microRNA (miRNA) and gene expression profiling during adipocytic differentiation of hMSC, and utilized bioinformatics as well as functional and biochemical assays, and identified several novel miRNAs differentially expressed during adipogenesis. Among these, miR-320 family (miR-320a, 320b, 320c, 320d and 320e) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 54 publications
4
91
0
Order By: Relevance
“…miR-320a overexpression significantly reduced osteoblastic differentiation, whereas miR-320a inhibition had the opposite effects. It is reported that miR-320 family members are upregulated during adipocyte differentiation of hMSCs, and overexpression of miR-320c promotes adipocytic differentiation of hMSCs [32]. This study together with our findings showing that miR-320a inhibits osteogenesis supports a role for miR-320 in cell lineage determination by promoting the adipogenic and inhibiting the osteogenic phenotype.…”
Section: Discussionsupporting
confidence: 71%
“…miR-320a overexpression significantly reduced osteoblastic differentiation, whereas miR-320a inhibition had the opposite effects. It is reported that miR-320 family members are upregulated during adipocyte differentiation of hMSCs, and overexpression of miR-320c promotes adipocytic differentiation of hMSCs [32]. This study together with our findings showing that miR-320a inhibits osteogenesis supports a role for miR-320 in cell lineage determination by promoting the adipogenic and inhibiting the osteogenic phenotype.…”
Section: Discussionsupporting
confidence: 71%
“…miR-125b-5p, miR-30e-3p and miR-204-5p), whereas several of them (e.g. miR-93-5p and miR-203-3p) had been reported to negatively regulate osteogenesis (Table S3) (Kennell et al, 2008;Hamam et al, 2014;Yang et al, 2012;. Eguchi et al also analyzed the miRNAs in adipocytes derived from EVs and detected several adipogenic miRNAs (including miR-148a-3p, miR-181a-5p, miR30a-5p, miR-125b-5p) (Eguchi et al, 2016), which is consistent with our results (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-30a is a positive regulator of adipocyte lineage commitment that acts through modulation of Runx2 while miR-143 is required for terminal differentiation by modulating MAP2K5-ERK5 (ERK5 is also known as MAPK7) signaling Chen et al, 2014;Hamam et al, 2014). In addition, exosomal miRNAs also contribute to the process of cell differentiation (Forterre et al, 2014;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-196a, miR-335-5p, miR-322, miR-26a, miR-26b, miR-29b, miR-1192, miR-218, miR-378, miR-548d-5p and miR-302a accelerate osteogenic differentiation [14][15][16][17][18][19][20][21][22], while miR-26a, miR-133, miR-135b, miR-138, the miR-30 family, miR-155, miR-100, miR-433, miR-145, miR-143, miR-542-3p, miR-338-3p, miR-140-5p and miR-146a impair osteoblast differentiation [23][24][25][26][27][28][29][30][31][32][33][34][35]. Many miRNAs have been reported to be involved in the regulation of adipogenic differentiation, such as miR-143, miR-17-92, miR-130, miR-138, miR-17-5p, miR-106a, miR-210, miR-709, miR-137, and miR-302 [36][37][38][39][40][41][42][43][44]. However, few miRNAs have been reported in association with obesity and the positive regulation of adipogenesis [45].…”
Section: Introductionmentioning
confidence: 99%